Relationship of Parental Acceptance-Rejection and Psychological Adjustment in Children and Adolescents with Congenital Heart Disease - Naz, Samia; Saeed, Hina; Anwar, Hira (Journal of Development and Social Sciences, 2024)
The study’s objective was to investigate the connection between psychological adjustment and parental acceptance/rejection in children and adolescents with congenital heart disease. Literature depicted that there is a significant association of Parental Acceptance-Rejection in children and adolescent psychological adjustment. The Sample of (N=240) from age range of 7 to 18 was taken from different cardiac units, clinics and schools which was consisted of two groups: patient group (n=120) and sibling group (n=120) from same parents, having same gender and same age bracket were taken for this study. Convenient purposive sampling technique was used. The study included children and adolescents with congenital cardiac disease.Short form of child version of Parental Acceptance-Rejection Questionnaire PARQ (Rohner, 2015) & Personal Assessment Questionnaire PAQ (Rohner, 2016) Urdu version and Demographic sheet was administered for data collection. The analysis’ findings demonstrated a highly substantial correlation between psychological adjustment and parental acceptance or rejection.Parental acceptance is positively correlated with children and adolescents’ emotional instability and emotional responsiveness. Future researchers can take into account longitudinal researches for determining the level of parental-acceptance rejection and psychological adjustment among children to develop coping strategies and interventions for such families.